2016
DOI: 10.1186/s41200-016-0071-0
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of the Smallscale Codlet, Bregmaceros nectabanus in the Mediterranean Sea, previously misidentified as B. atlanticus in this region

Abstract: Background: We report the occurrence of Bregmaceros nectabanus as the only species of this genus occurring in the Mediterranean Sea. Results: All previously published records of B. atlanticus from the Mediterranean are based on misidentifications. Among the features that distinguish B. nectabanus are its nearly unpigmented abdomen, presence of a thin dorsolateral longitudinal stripe below the second dorsal fin, and a distally fimbriate opercular spine.Conclusions: Since this species is known also from the Red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Goren and Galil (2008) doubted its status as an invader because of its scarce and patchy records in the Mediterranean; instead, they proposed that it was introduced in ballast water. Harold and Golani (2016) reviewed these identifications and argued that all previous records of Bregmaceros belong in fact to B. nectabanus , which is a Red Sea species, and not B. atlanticus , which is an Atlantic species.…”
Section: Discussionmentioning
confidence: 99%
“…Goren and Galil (2008) doubted its status as an invader because of its scarce and patchy records in the Mediterranean; instead, they proposed that it was introduced in ballast water. Harold and Golani (2016) reviewed these identifications and argued that all previous records of Bregmaceros belong in fact to B. nectabanus , which is a Red Sea species, and not B. atlanticus , which is an Atlantic species.…”
Section: Discussionmentioning
confidence: 99%
“…Zarrad et al. () reported that larval anchovies were mostly present in deeper areas in the Southwestern Mediterranean, whereas a recent epipelagic lessepsian fish, Bregmaceros nectabanus (Harold & Golani, ) and shelf dwellers such as Sparids and Gobiids (Froese & Pauly, ) were mostly present in the shallower sides of Iskenderun Bay.…”
Section: Discussionmentioning
confidence: 99%
“…Anchovy was another example of a similar case; even though its early life stages were present throughout the bay, they were particularly abundant around the entrance. Zarrad et al (2013) reported that larval anchovies were mostly present in deeper areas in the Southwestern Mediterranean, whereas a recent epipelagic lessepsian fish, Bregmaceros nectabanus (Harold & Golani, 2016) and shelf dwellers such as Sparids and Gobiids (Froese & Pauly, 2017) were mostly present in the shallower sides of Iskenderun Bay.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, Bregmaceros atlanticus Goode & Bean (1886) was considered as the only representative in the Mediterranean Sea. According to Harold & Golani (2016) all the records of Bregmaceros atlanticus from the Mediterranean Sea have been misidentifications of the smallscale codlet Bregmaceros nectabanus Whitley (1941). In the Mediterranean, the species was first mentioned from the Straits of Sicily, a record considered rather uncertain.…”
Section: First Record Of Smallscale Codlet Bregmaceros Nectabanus Whimentioning
confidence: 99%